A history of women in men's clothes : from cross-dressing to empowerment - Shopland, Norena (Pen & Sword History, 2021)
"Traditionally, historic women have been seen as bound by social conventions, unable to travel unless accompanied and limited in their ability to do what they want when they want. But thousands of women broke those rules, put on banned clothing and travelled, worked and even lived whole lives as men. As access to novels and newspapers increased in the nineteenth century so did the number of women defying Biblical and social restrictions. They copied each other's motives and excuses and moved into the world of men. Most were working-class women who either needed to or wanted to, break away from constricted lives; women who wanted to watch a hanging or visit a museum, to see family or escape domestic abuse, some wanted to earn a decent living when women's wages could not keep a family. The reasons were myriad. Some were quickly arrested and put on display in court, hoping to deter other women from such shameful behaviour, but many more got away with it. For the first time, A History of Women in Men's Clothes looks at those thousands of individuals who broke conventions in the only way they could, by disguising themselves either for a brief moment or a whole life. Daring and bold, this is the story of the women who defied social convention to live their lives as they chose, from simply wanting more independence to move and live freely, to transgender and homosexual women cross-dressing to express themselves, this is women's fight to wear trousers."--